Integral equations in the linear theory of elasticity in semiinfinite domains - Gomilko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate linear integral equations on a semiaxis that appear in the course of construction of solutions of boundary-value problems in the theory of elasticity in such domains as a semiinfinite strip or a cylinder. By using the Mellin transformation and the theory of perturbations of linear operators, we establish general results concerning the solvability and asymptotic properties of solutions of the equations considered. We give examples of application of the general statements obtained to specific integral equations in the theory of elasticity.